(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2017)
In this paper we consider the rst order nonlinear neutral dierence equation with maxima of the form: and established some sucient conditions for the oscillation of all solutions of the above equation. Examples are provided to illus-trate the main results. 2010 AMS Subject